Parents Reaching Out to Parents: An Appreciative, Qualitative Evaluation of Stakeholder Experiences of the Parent Champions in the Community Project - Bernie Carter; Anita Flynn; Jacqueline McKenna (MDPI AG, 2022)
Background: Bronchiolitis is a seasonal, global acute lower respiratory tract infection caused by respiratory syncytial virus (RSV) and is a leading cause of hospital admission in young children. A peer-led (parents to parents) intervention was implemented to empower parents of children at risk of bronchiolitis and reduce hospital admissions. This paper reported the evaluation that aimed to gain the perspectives and experiences of five key stakeholder groups. Methods: A qualitative remote interview-based design, informed by Appreciative Inquiry was used. Thematic analysis was used. Results: Sixty-five stakeholders participated: parents (n = 43; mothers, n = 42), Parent Champions (n = 9), Children's Centre Managers (n = 8), Children's Centre Group Leaders (n = 11), and Core Team (n = 4). An overarching theme 'Parents reaching out to parents' was supported by five sub-themes (Raising awareness and sharing knowledge; Creating connection, trust, and confidence; Flourishing in their role as a Parent Champion; Rising to the challenges; and Knowledge is power, prevention is key: the government needs to know this.) Conclusions: Parent-to-parent peer support via the Parent Champions was perceived positively by parents who wanted to learn and improve the lives and health of their children. Parent Champions were successful in delivering information. Considering the socioeconomic burden of bronchiolitis to services and families, the potential for an upstream, relatively low cost, high-reach innovative intervention, as evidenced in this project, seems a valuable opportunity for improving children's respiratory health.